An Analysis of Al-Djurjani’s Definition of Identity – huwiyya: The then and Now - Ertugrul Gokcekuyu (Alsuna: Journal of Arabic and English Language, 2021)
Purpose - This paper aims to answer in what ways such an early account of huwiyya may overlap or have similarities with some of the modern, yet ambiguous depictions of the term. Design/methodology/approach - The research design is descriptive-qualitative research. The data gained are written words and sentences from al-Djurjani’s works. Findings - Literature today acknowledges more progressive interpretations of identity, wherein the phrase has been used in ambiguous ways, categorizing the individual in existential, contextual, and perceptual terms attempting to understand the inner and outer workings of the Self. Most definitions of identity in social sciences assume the phrase to be a unit of analysis; a challenging task when the phrase is so heterogeneous. The point of departure in this article is Al-Djurdani’s two-layered live wire definition that connotes a binary reading. While the first layer of this - one of the earliest - Muslim philosophical definitions is existentialist, the second layer merits a reading that is modestly contextual. Originality/value - The point of departure in this article is Al-Djurdani’s two-layered live wire definition that connotes a binary reading. While the first layer of this - one of the earliest - Muslim philosophical definitions is existentialist, the second layer merits a reading that is modestly contextual. Paper type – Concept paper